Tower of Babble : How the United Nations has Fueled Global Chaos - Gold, Dore (New York Crown Forum, 2004)
"Politicians and pundits are imploring the United States to give the UN a major role in American foreign policy. But as bestselling author Dore Gold reveals in Tower of Babble, it is absurd to look to the UN to fight aggression, combat terrorism, and preserve global order. The UN is an abject failure - a fatally flawed organization that has actually accelerated and spread global chaos.
Include Illustrations, Maps, Appendix, Notes and Index
History
Keywords: Security, International -- World Politics -- United Nations